2022
DOI: 10.3389/fnbeh.2021.793115
|View full text |Cite|
|
Sign up to set email alerts
|

Seeing What I Did (Not): Cerebral and Behavioral Effects of Agency and Perspective on Episodic Memory Re-activation

Abstract: Intuitively, we assume that we remember episodes better when we actively participated in them and were not mere observers. Independently of this, we can recall episodes from either the first-person perspective (1pp) or the third-person perspective (3pp). In this functional magnetic resonance imaging (fMRI) study, we tested whether agency and perspective modulate neural activity during memory retrieval and subsequently enhance memory performance. Subjects encoded a set of different episodes by either imitating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…In recent work investigating the role of agency in episodic remembering, Jainta et al (2022) reveal findings that run counter to McCarroll's (2018) enrichment proposal. Their study investigated the level of prediction error in episodic recall.…”
Section: Agencymentioning
confidence: 73%
See 2 more Smart Citations
“…In recent work investigating the role of agency in episodic remembering, Jainta et al (2022) reveal findings that run counter to McCarroll's (2018) enrichment proposal. Their study investigated the level of prediction error in episodic recall.…”
Section: Agencymentioning
confidence: 73%
“…Though remembering-from-the-outside is the most advanced theory of memory perspective on offer, it faces some issues. Notably, emerging empirical evidence suggests that information about one's visual perspective might not be encoded in memory traces at all (Jainta et al 2022). We will review these and other findings in the next section.…”
Section: Memory Perspective In Recent Philosophical Debatesmentioning
confidence: 99%
See 1 more Smart Citation
“…This research extends previous findings on effects of agency in relation to memory and cognition. Although agency has been found to influence visual attention ( Huffman & Brockmole, 2020 ; Wen & Haggard, 2018 ), object vision ( Haxby et al, 2020 ; Thorat et al, 2019 ), face perception ( Walker & Keller, 2019 ), autobiographical memory ( Woike et al, 1999 ; Woike & Polo, 2001 ), hippocampal responses to expectation violations in episodic memory ( Jainta et al, 2022 ), and memory performance ( Hon & Yeo, 2021 ; Hornstein & Mulligan, 2001 ), this research suggests that effects of agency, at least as part of the stimulus, on cognition do not or only weakly extend to the formation of memory representations in episodic memory by influencing binding processes. Importantly, we focused on agency as part of an (external) stimulus, whereas the majority of previous research has focused on the agency of the participant (e.g., see the enactment effect, Engelkamp, 1986 ; Hornstein & Mulligan, 2001 ; Roberts et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Agentic-motivated individuals reported memories that were more congruent with their motives and structured them using more differentiation. Jainta et al (2022) found effects of agency during encoding on episodic memory. When encoding different episodes by imitating or merely observing videos showing short stories, participants exhibited stronger hippocampal responses to expectation violations when they were actors rather than observers in the episode.…”
mentioning
confidence: 99%